2013
DOI: 10.1128/jb.00199-13
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Hemoglobin Binding and Heme Utilization by a Bacterial Hemoglobin Receptor

Abstract: Iron is an essential nutrient for most living organisms. To acquire iron from their environment, Gram-negative bacteria use TonB-dependent transporters that bind host proteins at the bacterial surface and transport iron or heme to the periplasm via the Ton machinery. TonB-dependent transporters are barrel-shaped outer membrane proteins with 22 transmembrane domains, 11 surface-exposed loops, and a plug domain that occludes the pore. To identify key residues of TonB-dependent transporters involved in hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…6, step 2). Consistent with this idea, mutagenesis studies of the Hb receptor A (HgbA) from Gram-negative Haemophilus ducreyi indicate that there is likewise a physical separation of the Hb-binding and heme uptake interfaces (66,67). This similarity suggests that an architecture involving multiple interaction interfaces might have a functional advantage for heme extraction from Hb in a range of systems.…”
Section: Discussionmentioning
confidence: 87%
“…6, step 2). Consistent with this idea, mutagenesis studies of the Hb receptor A (HgbA) from Gram-negative Haemophilus ducreyi indicate that there is likewise a physical separation of the Hb-binding and heme uptake interfaces (66,67). This similarity suggests that an architecture involving multiple interaction interfaces might have a functional advantage for heme extraction from Hb in a range of systems.…”
Section: Discussionmentioning
confidence: 87%
“…Site-directed mutagenesis studies of TBDT HgbA from Haemophilus ducreyi demonstrate that motifs in the extracellular loops are required to bind hemoglobin, a prerequisite to heme transfer 19,32 . Thus, removal of an essential extra-cellular loop region of ShuA was expected to disrupt the ShuA-hemoglobin interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Iron acquisition is an important aspect of pathogenesis for many pathogens, and bacterial strategies for the acquisition of iron have been described for many decades [ 24 ]. It has been shown that the inactivation of genes involved in iron acquisition in Shigella [ 25 ], Y .…”
Section: Discussionmentioning
confidence: 99%